1996
DOI: 10.1037/0021-843x.105.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and posttraumatic stress disorder in female victims of sexual and nonsexual assault.

Abstract: Judgmental biases for threat-relevant stimuli are thought to be important mechanisms underlying the etiology and maintenance of anxiety disorders. The authors hypothesized (a) that people with generalized social phobia (GSP) would rate negative social events but not nonsocial events as more probable and costly than would nonanxious controls (NACs) and (b) that cognitive behavioral treatment would decrease probability and cost estimates for social but not nonsocial events. Participants with GSP and NACs were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
119
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 18 publications
15
119
2
2
Order By: Relevance
“…However, such a model had not been examined previously in a South African setting. It has been suggested that the use of avoidant coping strategies may help to explain the relationship between PTSD and substance use (Santello and Leitenberg, 1993;Ullman et al, 2007;Valentiner et al, 1996). This deserves further investigation in the South African setting, where it may help to inform culturally appropriate ways to break the cycle between trauma and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a model had not been examined previously in a South African setting. It has been suggested that the use of avoidant coping strategies may help to explain the relationship between PTSD and substance use (Santello and Leitenberg, 1993;Ullman et al, 2007;Valentiner et al, 1996). This deserves further investigation in the South African setting, where it may help to inform culturally appropriate ways to break the cycle between trauma and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that PTSD can be conceptualised as indicative of incomplete emotional processing. In support, many researchers have found that affective and cognitive suppression commonly occurs in individuals after a trauma and this can be adaptive at the time of the trauma (e.g., Bryant & Harvey, 1995 ;Solomon et al, 1988;Valentiner et al, 1996). Yet, suppression over an extended period of time is considered to be maladaptive as it interferes with processing the emotions associated with the trauma, and impedes recovery overtime (e.g.…”
Section: Emotionmentioning
confidence: 99%
“…Immediate posttrauma coping strategies have been found to predict the subsequent onset of PTSD (Clohessy & Ehlers, 1999;Valentiner, Foa, Riggs, & Gershuny, 1996); male and female participants might differ in this respect (see Vingerhoets & Van Heck, 1990). For example, female paramedics were more likely than their male counterparts to report using the coping strategies of wishful thinking, mental disengagement, and suppression of trauma memories.…”
Section: Other Variables Of Potential Interestmentioning
confidence: 99%